A history of the new India - Irschick, Eugene F. (Routledge, 2015)
"Providing a different approach to the history of India than previously advocated, this textbook argues that there was a constant interaction between peoples and cultures. This interactive, dialogic approach provides a clear understanding of how power and social relations operated in South Asia. Covering the history of India from Mughal times to the first years of independence, the book consists of chapters divided roughly between political and thematic questions. Topics discussed include: Mughal warfare and military developments; the construction of Indian culture; Indian, regional and local political articulation; India's independence and the end of British Rule; the growth of the Hindu Right; the dispute over Kashmir; as well as a detailed timeline that provides a useful overview to key events in the history of India. A set of background reading is included after each chapter for readers who wish to go beyond the remit of this text. Written in an accessible, narrative style, the textbook will be suitable in courses on Indian and South Asian History, as well as courses on World History and South Asian Studies. Eugene F. Irschick is professor of history at University of California, Berkeley. In his research and published works, such as Dialogue and History : Constructing South India, 1795-1895 (1994), he suggests that the production of history and political structures is dialogic. He has been teaching courses on Indian history at UC Berkeley for 16 years. Much of the time during his early teaching years was focused on minority and separatist politics in south India during the 20th century. Recently, he has been teaching courses on women's history in South Asia as well as courses on post-colonialism"--Provided by publisher.